2010
DOI: 10.1063/1.3350900
|View full text |Cite
|
Sign up to set email alerts
|

Increased induction in FeCo-based nanocomposite materials with reduced early transition metal growth inhibitors

Abstract: We report on new high-saturation induction, high-temperature nanocomposite alloys with reduced glass formers. The amounts of the magnetic transition metals and early transition metal growth inhibitors were systematically varied to determine trade-offs between higher inductions and fine microstructures with consequently lower magnetic losses. Alloys of nominal composition ͑Fe 65 Co 35 ͒ 79.5+x Nb 4−x B 13 Si 2 Cu 1.5 ͑x=0-4͒ were cast into a 28 mm wide, 20 m thick ribbon from which toroidal cores were wound. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Nanocomposite alloys (HTX002-type [1][2][3] ) of composition (Fe 65 Co 35 ) 79.5þx B 13 Nb 4Àx Si 2 Cu 1.5 (x ¼ 0-4) and (Fe 65 Co 35 ) 83 B 10 Nb 4 Si 2 Cu 1 , designated alloy "10-4", were studied to determine the kinetics of and phase evolution in secondary crystallization. HTX002 nanocomposites exhibit high saturation flux densities up to 1.85 T and low losses at kHz level frequencies, [1][2][3] making them promising for inductive components in high frequency power electronic applications. The formation of crystalline phases other than a-FeCo deteriorate these properties.…”
Section: Introductionmentioning
confidence: 99%
“…Nanocomposite alloys (HTX002-type [1][2][3] ) of composition (Fe 65 Co 35 ) 79.5þx B 13 Nb 4Àx Si 2 Cu 1.5 (x ¼ 0-4) and (Fe 65 Co 35 ) 83 B 10 Nb 4 Si 2 Cu 1 , designated alloy "10-4", were studied to determine the kinetics of and phase evolution in secondary crystallization. HTX002 nanocomposites exhibit high saturation flux densities up to 1.85 T and low losses at kHz level frequencies, [1][2][3] making them promising for inductive components in high frequency power electronic applications. The formation of crystalline phases other than a-FeCo deteriorate these properties.…”
Section: Introductionmentioning
confidence: 99%
“…The quantified correlation of local composition with nanostructure done here is applicable to previous qualitative reports [8], [11]. Moreover, the models developed, techniques used, and the overall trends presented here are applicable to the whole range of magnetic nanocomposite materials.…”
Section: Methodsmentioning
confidence: 90%
“…Samples designated HTX002 developed to maximize saturation induction, of composition (Fe 65 Co 35 ) 79.5 B 13 Si 2 Nb 4 Cu 1.5 , were synthesized [8], [11], [20]. The alloy exhibits relative permeability >1200, saturation induction of 1.76 T, and power loss of 10 W/g at 0.2 T and 20 kHz.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,[8][9][10][11] In prior research, we have observed the crystallite size to become finer with the addition of Nb, resulting in the development of materials with a low core loss. 12 The nanocrystallization process of HITPERM alloys is quite different than that of FINEMET alloys. 13 It is reported that Cu clustering is strongly reduced in FINEMET alloys by the substitution of Fe by Co, 14 although in other Co-rich alloys the density of Cu clusters is insufficient to explain the copious nucleation in these alloys.…”
mentioning
confidence: 99%